The Determinants of Teachers’ Well-Being: The Mediating Role of Mental Fatigue - Guglielmi, Dina; Panari, Chiara; Simbula, Silvia (European Journal of Mental Health, 2012)
The Mediating Role of Mental Fatigue: In recent years, many studies have focused on the determinants and consequences of teacher stress. One of the most recent theoretical models concerning stress is the Job Demands-Resources (JDR) model. This study examines one process – namely the energetic process – which supposes that high job demands exhaust employees’ mental and physical resources and therefore cause ill health. Particularly, this study examines the mediating role of mental fatigue between three job demands of teachers (workload, inequity and work/family conflict) and three consequences of stress: psychological and physical symptoms and work satisfaction. An Italian version of the self-report Questionnaire for Psychosocial Work Environment and Stress (PWSQ) was administered to 697 teachers belonging to a random sample of 17 school organizations. The results showed that mental fatigue has a mediating role in the relationship between work/family conflict and the three outcomes considered, namely psychological and physical symptoms, and work satisfaction. This study has an important implication for intervention strategy because mental fatigue is a pre-strain condition which arises before more intense outcomes, such as stress-related diseases occur. Identification of this condition allows prevention of the consequences of stress.